Impact Of The Chemical And Hormonal Composition Of Pollen From Different Date Palm Cultivars At Different Maturity Stages On The Ripening Of Barhi Fruits Propagated Through Tissue Culture - Al-Hmood, Firas M.; Ati, Muntaha A.; Abd, Abdulkareem M. (Basrah Journal Of Date Palm Research, 2023)
The study was carried out in an orchard in Al-Sibah area/ Abu Al-Khasib district/ Basrah Governorate. Three male cultivars of date palm Phoenix dactylifera L. were involved, including the red Ghanami, the common khukri, and the Canary, at different maturity: early, medium, and late. The content of pollen of hormones and free amino acids and their effect on the maturity rate were studied. Results revealed significant differences regarding the pollen content among the three male cultivars at the different maturity stages. The pollen of the common Khukri and the early age demonstrated a significant superiority over the rest of the study factors in the levels of substances of resembling auxins and abscisic acid, recording 30.862 and 29.841 μg/kg, respectively. The interference between the Canary and the early maturity stage showed significant superiority in the pollen content of substances of resembling gibberellins, at 637.64 μg/kg. The interference between the red Ghanami and the mid maturity stage, the interference between the common Khukri and the late maturity stage, and the interference between the Canary and the early maturity stage showed the lowest level of substances of resembling auxins, gibberellins and abscisic acid, amounting 23.265, 154.81, and 25.17 μg/kg. Regarding the content of pollen of free amino acids, the interference between the Khukri and the early maturity stage showed the lowest rate at 7.59 mg/100 gm. The results also showed an effect for the hormonal and chemical content of pollens on the fruit ripening. The interference between a combination of red Ghanami variety + the common Khukri and the early maturity age of pollen produced significantly higher ripe fruits, recording 70.8%, but did not differ with the other interferences. Based on our results, the source of pollen has a significant role on palm productivity and fruit quality. The combination Ghanami and khukri can be used as pollinators for the flowers of date palms of the Barhi cultivar.